Measuring Social Capital : An Integrated Questionnaire - Grootaert, Grootaert (Washington, DC: World Bank, 2013)
The idea of social capital has enjoyed a remarkable rise to prominence in both the theoretical and applied social science literature over the last decade. While lively debate has accompanied that journey, thereby helping to advance our thinking and to clarify areas of agreement and disagreement, much still remains to be done. One approach that we hope can help bring further advances for both scholars and practitioners is the provision of a set of empirical tools for measuring social capital. The purpose of this paper is to introduce such a tool-the Integrated Questionnaire for the Measurement of Social Capital (SC-IQ)-with a focus on applications in developing countries. The tool aims to generate quantitative data on various dimensions of social capital as part of a larger household survey (such as the Living Standards Measurement Survey or a household income/expenditure survey). Specifically, six dimensions are considered: groups and networks; trust and solidarity; collective action and cooperation; information and communication; social cohesion and inclusion; empowerment and political action. The paper addresses sampling and data collection issues for implementing the SC-IQ and provides guidance for the use and analysis of data. The tool has been pilot-tested in Albania and Nigeria and a review of lessons learned is presented.